The rare ospC allele L of Borrelia burgdorferi sensu stricto, commonly found among samples collected in a coastal plain area of the southeastern United States, is associated with ixodes affinis ticks and local rodent hosts Peromyscus gossypinus and Sigmodon hispidus - Rudenko, Nataliia; Golovchenko, Maryna; Grubhoffer, Libor; Oliver, James H (Applied and environmental microbiology, 2013)
The rare ospC allele L was detected in 30% of Borrelia burgdorferi sensu stricto strains cultured from a tick species, Ixodes affinis, and two rodent host species, Peromyscus gossypinus and Sigmodon hispidus, collected in a coastal plain area of Georgia and South Carolina, in the southeastern United States.
Keywords: alely; Borrelia burgdorferi; Ixodes; DNA bakterií; Antigens, Bacterial; Peromyscus; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; klíště; antigeny bakteriální; Alleles; křeček rodu Peromyscus; Genotype; zvířata; Bacterial Outer Membrane Proteins; Southeastern United States; sekvenční analýza DNA; DNA, Bacterial; proteiny vnější bakteriální membrány; Sigmodontinae; genotyp; Animals; jihovýchod USA